Maternal Oxygen Supplementation Compared With Room Air for Intrauterine Resuscitation: A Systematic Review and Meta-analysis. Issue 9 (September 2021) - Raghuraman, Nandini; Temming, Lorene A.; Doering, Michelle M.; Stoll, Carolyn R.; Palanisamy, Arvind; Stout, Molly J.; Colditz, Graham A.; Cahill, Alison G.; Tuuli, Methodius G.
Abstract : (Abstracted from JAMA Pediatr 2021;175:368–376) In the United States, 2 of 3 pregnant women receive oxygen supplementation at some point during labor. It is provided to increase placental oxygen transfer and prevent neonatal acidemia when fetal heart rate (FHR) tracings suggest fetal hypoxia.